2016
DOI: 10.1089/vbz.2016.1985
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence ofBrucellaspp. in Cattle, Molecular Characterization in Milk, and the Analysis of Associated Risk Factors with Seroprevalence in Humans, Egypt

Abstract: The objective of the present study was to estimate the seroprevalence of Brucella spp. in humans and cattle at Sharkia Governorate, Egypt. In addition, identification of Brucella spp. in milk samples by PCR and culture with the evaluation of the risk factors associated with Brucella spp. seroprevalence in humans were carried out. Overall, the seroprevalence of Brucella antibodies in the examined cattle was 23.8%, while in human participants it was 21%. The examination of 205 milk samples using PCR revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…This may explain the occurrence of this biotype in camels in the current study which consider the most dominant biotype of Brucella isolated from both animals and human in Egypt as reported by (Mohamed and Eisa, 2004;Soliman, 2006;El-Diasty, 2009;El-Sayed et al, 2011;Abdel Hamid, 2012;Afifi et al, 2015, El-Diasty et al, 2016, El-Hady et al, 2016.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This may explain the occurrence of this biotype in camels in the current study which consider the most dominant biotype of Brucella isolated from both animals and human in Egypt as reported by (Mohamed and Eisa, 2004;Soliman, 2006;El-Diasty, 2009;El-Sayed et al, 2011;Abdel Hamid, 2012;Afifi et al, 2015, El-Diasty et al, 2016, El-Hady et al, 2016.…”
Section: Discussionsupporting
confidence: 69%
“…However, information about economic losses due to camel brucellosis is scarce. Although camels are not the primary host of Brucella, B. abortus and B. melitensis isolated from milk, aborted fetus, lymph nodes and vaginal swabs (Radwan et al, 1992;Gameel et al, 1993;Agab et al, 1994;Abou-Eisha, 2000;Hamdy and Amin, 2002;El-Gohary et al, 2016;El-Diasty et al, 2016;El-Hady et al, 2016). Disease transmission depends on Brucella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Rose Bengal Plate test (RBPT), the survey study published between 1948 and 2009 in Egypt the prevalence of Brucellosis in cows and buffaloes were 5.4 % [8]. Isolation of Brucella species is still the golden key for an accurate diagnosis to avoid the false positive reaction of serological diagnosis but long incubation period and samples handling act as barrier for this method in diagnosis [9].The most prevalent serotypes in Egyptian veterinary field are Brucella abortus biovar 1, next to B. melitensis biovar 3 [10]. Regarding the biochemical changes with B125rucellosis the available literature is little.…”
Section: Introductionmentioning
confidence: 99%
“…Belonging to households that owned a presumptively Brucella seropositive herd, signifi cantly increased the odds for probable Brucella seropositivity in household members by (2.03; 95% CI, 1.01, 4.07) and this is true since from literature it is known that animals are solely responsible for infecting human beings directly or indirectly [1,4], furthermore, studies have shown that interaction with infected animals causes infections in household members that rear livestock [8,38]. When animal reproductive materials are improperly disposed off in the open or given to dogs, this most likely exposes the dogs to infection [39].…”
Section: Discussionmentioning
confidence: 99%